Let $M\subset \mathbb{R}^k$ be a smooth $m$-manifold, and let $X$ be a smooth vector field on $M$. Let $\phi$ be the flow of $X$, defined via $\phi(t,p) := \gamma(t)$, with $\gamma(0) = p_0$ (where $\gamma(t)$ satisfies the equation $\dot{\gamma}(t) = X(\gamma(t))$.)

Let $Y$ be another vector field on $M$, with flow $\psi$. Set $\phi^s(\cdot) := \phi(s,\cdot)$, and $\psi^t$ analogously. Let $\beta(s,t) := \phi^s\circ\psi^t\circ\phi^{-s}\psi^{-t}(p)$, for some $p\in M$.

My professor now writes $$ \frac{\partial\beta}{\partial s}(0,t) = X(p) - d\psi^t(\psi^{-t}(p))X(\psi^{-t}(p))$$ I don't understand exactly how he is using the chain rule, etc., to get to this equation. I know that $$ \frac{d}{dt}\phi^t(p) = X(\phi^t(p)),\quad \phi^0(p)=p,$$ but I can't figure out the rest.


You professor uses the differential of a function defined by two variables:

$\Psi(s,s')=\phi_s\psi_t\phi_{-s'}\psi_{-t}$. Then compute $\partial_s\Psi(0,s')+\partial_{s'}\Psi(s,0)$ which gives the result.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.